Adhesions as a risk factor for postoperative morbidity in patients undergoing repeat hepatectomy and the potential efficacy of adhesion barriers. (27th September 2021) - Okubo, Satoshi; Shindoh, Junichi; Kobayashi, Yuta; Matsumura, Masaru; Hashimoto, Masaji
Abstract: Background: The actual efficacy of use of adhesion barriers during liver surgery remains to be fully understood. Methods: We conducted an extensive review of clinical data and operation videos of 210 patients who underwent repeat hepatectomy to clarify the factors associated with the degree of adhesion as evaluated by the TORAD score. Results: Adhesion barriers were placed in 131 patients (Seprafilm ® [n = 77], Adspray ® [n = 32], and Interceed ® [n = 22)]), but not in the remaining 79 patients during the previous surgery. Multivariate analysis identified a high adhesion severity score at relaparotomy as being associated with an increased risk of postoperative global morbidity (odds ratio [OR], 1.75 per +1 point, P < .001) and major morbidity (OR, 1.88 per +1 point; P < .001), and use of an adhesion barrier at the previous surgery as being an independent predictor of a low adhesion severity score (OR, 0.21; P < .001). Use of adhesion barriers showed tendency toward lower adhesion severity scores at relaparotomy as compared to the control group, irrespective of the type of adhesion barrier used. Conclusion: A high degree of adhesion formation was directly associated with an increased risk of postoperative morbidity after relaparotomy, and use of adhesion barriers appears to reduce the extent of adhesion. Abstract : Highlight A high degree of adhesion formation around the liver was shown to be associated with an increased risk of postoperative morbidity after repeat hepatectomy. Okubo and colleagues found that the use of adhesion barriers significantly reduced the extent of adhesion at re‐laparotomy, irrespective of the type of adhesion barrier used.